Hospital Matarazzo: trajetória, associativismo e patrimônio italiano em São Paulo (séculos XIX, XX e XXI) - Brambilla, Thaís Teixeira Dias (2024)
This thesis aims to trace two distinct moments in the history of the Matarazzo Hospital. The first is related to the creation of the hospital, beginning with the immigration process to São Paulo, the Italian associativism, and the foundation and expansion of what was then called Hospital Umberto Primo. After a four-decade leap, the subjects addressed refer to the economic crisis and the closure of the hospital, including discussions on heritage matters. In the face of the outflows of emigrants from Italy, Brazil was one of the receiving countries for this community, with those arriving in the state of São Paulo and the city itself standing out. They came in search of better living conditions and settled in the state's interiors, on coffee farms, and also in cities, working as laborers, craft professionals, in commerce, and in various branches and activities, also as entrepreneurs and industrialists. The increase in flows through migratory networks allowed the formation of multiple associations, among which the Società Italiana di Beneficenza in San Paolo stood out, managing to unite Italians from different regions, professions, and social classes in favor of creating health care actions. This society created the Umberto Primo hospital, later named Matarazzo Hospital. The construction was made possible by the benevolence of Italian businessmen and industrialists, notably Count Francesco Matarazzo. Inaugurated in 1904, it underwent expansions and renovations throughout its operation. For nearly a century, the hospital served, according to its statute, "without distinction of race, creed, or nationality." In 1986, the institution's reputation was shaken by the "INAMPS Scandal," a delicate moment when the hospital superintendent was accused of fraud, leading to the hospital's temporary closure, with resistance from its employees towards resuming activities. The intensification of the crisis led to the cessation of activities in 1993, and the hospital was abandoned until 1996 when it was purchased by Previ (Pension Fund of the Employees of Banco do Brasil), which sought to create a new commercial venture on the site, unsuccessfully, leading to the abandonment of the buildings, which in 1998 were occupied by the Homeless Movement. In 2010, speculations began about negotiations for sale, which was finalized in 2011 with the purchase by the Allard Group, which started the Cidade Matarazzo project. The project and the start of the works generated controversies regarding the issue of the hospital as a historical heritage. Its importance was recognized by Condephaat (1986), which considered the hospital as a remnant of the architecture and Italian presence in the city. Thus, the thesis seeks to track and discuss the difficulties faced in maintaining the buildings and to discuss the processes of heritage listing and review, which allowed the creation of a new project for the buildings that excluded their use as a hospital